2015
DOI: 10.3344/kjp.2015.28.2.122
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Techniques for Ultrasound-guided Caudal Injection: The Influence of the Depth of the Inserted Needle on Caudal Block

Abstract: BackgroundCaudal epidural injections have been commonly performed in patients with low back pain and radiculopathy. Although caudal injection has generally been accepted as a safe procedure, serious complications such as inadvertent intravascular injection and dural puncture can occur. The present prospective study was designed to investigate the influence of the depth of the inserted needle on the success rate of caudal epidural blocks.MethodsA total of 49 adults scheduled to receive caudal epidural injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…This success rate may exceed that of fluoroscopically guided injections. With use of ultrasound guidance to place the needle with a cephalad orientation through the cornua 9/29 (31%) had initial blood return in one study (14) and at least 5/25 (25%) in another (15). However, although aspiration for blood likely reduces the incidence of intravascular drug injection, it is not sufficient to prevent intravascular injection (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This success rate may exceed that of fluoroscopically guided injections. With use of ultrasound guidance to place the needle with a cephalad orientation through the cornua 9/29 (31%) had initial blood return in one study (14) and at least 5/25 (25%) in another (15). However, although aspiration for blood likely reduces the incidence of intravascular drug injection, it is not sufficient to prevent intravascular injection (5).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have suggested that caudal epidural injection may be more safely performed with Doppler monitor than with fluoroscopic guidance through decreasing the risk of intravascular injection, one by use of Doppler flow confirmation of an epidural pattern (5) and one by injecting immediately after penetrating the sacrococcygeal membrane to avoid contact with the venous plexus (15). This study adds another method to avoid intravascular injection, by inserting the needle at a 90 degree angle to the plexus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sir —The incidence of caudal block failure is about 1% and anatomical variation is a major contributing factor . We had an experience of caudal block failure in an 18‐month‐old male (16 kg) child with a pelvic neuroblastoma.…”
mentioning
confidence: 99%
“…Ram Doo et al . during fluoroscopic‐guided injection of dye in the caudal space found an atypical pattern due to adhesions and fibrosis.…”
mentioning
confidence: 99%